2021
DOI: 10.1111/cup.14163
|View full text |Cite
|
Sign up to set email alerts
|

PRAME expression in cellular neurothekeoma: A study of 11 cases

Abstract: Background: Preferentially expressed antigen in melanoma (PRAME) has been widely investigated in the skin, mainly in melanocytic tumors, and constitutes an aid in differentiating benign from malignant lesions. Very few studies have been performed on non-melanocytic tumors. Materials:We investigated the immunohistochemical expression of PRAME on a series of 11 neurothekeomas (NTKs), together with 3 cases of nerve sheath myxoma (NSM) and 1 case of plexiform fibrohistiocytic tumor (PFT), in order to evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
(49 reference statements)
1
8
0
Order By: Relevance
“…This is consistent with the previously reported pattern of PRAME expression in squamous cell carcinoma [19]. PRAME is not specific to a cell lineage and has been described in tumors of non-melanocytic origin including colon adenocarcinoma, cellular neurothekeoma, and some lymphomas [20][21][22]. Not surprisingly, expression of PRAME was identified in several of our non-melanocytic lesions.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with the previously reported pattern of PRAME expression in squamous cell carcinoma [19]. PRAME is not specific to a cell lineage and has been described in tumors of non-melanocytic origin including colon adenocarcinoma, cellular neurothekeoma, and some lymphomas [20][21][22]. Not surprisingly, expression of PRAME was identified in several of our non-melanocytic lesions.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, 1 study 8 shows a very low expression of PRAME inferior to 1% of cells in 5 of the 8 cases of lentigo malignant tested. On the other hand, some studies 5,7–10 have underlined that a minority of benign melanocytic nevi (between less than 10% to 20%) show a focal expression of PRAME with a great variability in the distribution of the positive cells from case to case between 1 to lesser than 75% of cells. In addition, the diffuse…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, other studies have reported that immunostaining for PRAME can also be used in other neoplastic settings, including soft tissue sarcomas [ 8 ], non-small cell lung cancer [ 9 ], breast carcinoma [ 10 ], renal cell carcinoma [ 11 ], ovarian carcinoma [ 12 ], leukemia [ 13 ] and synovial sarcoma [ 14 ]. In this background, the importance and use of PRAME in non-melanoma skin cancer skin lesions have not yet been reported in the literature, with only a few works that have tried to shed light on the topic [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%